Local government status and viability implications for Nigeria: A qualitative approach (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The current status of local governments in Nigeria where there are tied to the apron strings of state governors has adverse implications for rural development, cutting across political, economic and social domains. This has resulted to their inability to render essential services required for rural development. The objective of this study was to determine the factors that render local governments in Nigeria non-viable and to ascertain what would make them viable as third tier governments as enshrined in the 1999 constitution of the federal republic of Nigeria. The qualitative method of data analysis was applied, using mixed methods such as Key Informant Interview (KII) and documentary method to draw data. The paper found that local governments in Nigeria are not viable due to the usurpation of their functions by state governments, fiscal imbalances, challenges arising from state local government joint accounts, formation of care taker/transition committees, and failure of the federal and state government to grant local government autonomy. Consequent upon these findings, the paper concludes that a framework that encompasses full local government autonomy, equitable sharing of federal revenue allocationsand fiscal earnings among the federating units, eradication of State Local Government Joint Account and care taker committees in local government councils, sustenance of democratic structures in all local governments and the resilience to beef up internally generated revenue of local governments are recommended to make local governments viable.
Keywords: Local government viability; Local government autonomy; State local government joint account; Rural development; Rural impoverishment